Bone regeneration by means of a three-dimensional printed scaffold in a rat cranial defect - Kwon, Doo Yeon; Park, Ji Hoon; Jang, So Hee; Park, Joon Yeong; Jang, Ju Woong; Min, Byoung Hyun; Kim, Wan Doo; Lee, Hai Bang; Lee, Junhee; Kim, Moon Suk (Journal of Tissue Engineering and Regenerative Medicine, 2018)
Recently, computer-designed three-dimensional (3D) printing techniques have emerged as an active research area with almost unlimited possibilities. In this study, we used a computer-designed 3D scaffold to drive new bone formation in a bone defect. Poly-L-lactide (PLLA) and bioactive β-tricalcium phosphate (TCP) were simply mixed to prepare ink. PLLA + TCP showed good printability from the micronozzle and solidification within few seconds, indicating that it was indeed printable ink for layer-by-layer printing. In the images, TCP on the surface of (and/or inside) PLLA in the printed PLLA + TCP scaffold looked dispersed. MG-63 cells (human osteoblastoma) adhered to and proliferated well on the printed PLLA + TCP scaffold. To assess new bone formation in vivo, the printed PLLA + TCP scaffold was implanted into a full-thickness cranial bone defect in rats. The new bone formation was monitored by microcomputed tomography and histological analysis of the in vivo PLLA + TCP scaffold with or without MG-63 cells. The bone defect was gradually spontaneously replaced with new bone tissues when we used both bioactive TCP and MG-63 cells in the PLLA scaffold. Bone formation driven by the PLLA + TCP30 scaffold with MG-63 cells was significantly greater than that in other experimental groups. Furthermore, the PLLA + TCP scaffold gradually degraded and matched well the extent of the gradual new bone formation on microcomputed tomography. In conclusion, the printed PLLA + TCP scaffold effectively supports new bone formation in a cranial bone defect.
Keywords: 3-D printing; 3D-printing; Bioactives; Bone defect; Bone formation; Bone regeneration; Neo-bone formation; Poly (l-lactide); Printed scaffold; Tri-calcium phosphates; Animals; Bone Regeneration; Cell Adhesion; Cell Line, Tumor; Cell Proliferation; Fluorescence; Humans; Osteogenesis; Polyesters; Printing, Three-Dimensional; Rats, Sprague-Dawley; Reproducibility of Results; Skull; Tissue Engineering; Tissue Scaffolds; X-Ray Microtomography; 3D printing; bone regeneration; imaging; ink; neo-bone formation; printed scaffold